Validation of Bedaquiline Phenotypic Drug Susceptibility Testing Methods and Breakpoints: a Multilaboratory, Multicountry Study - Kaniga, Koné; Aono, Akio; Borroni, Emanuele; Cirillo, Daniela Maria; Desmaretz, Christel; Hasan, Rumina; Joseph, Lavania; Mitarai, Satoshi; Shakoor, Sadia; Torrea, Gabriela; Ismail, Nazir Ahmed; Omar, Shaheed V (Journal of clinical microbiology, 2020)
Drug-resistant tuberculosis persists as a major public health concern. Alongside efficacious treatments, validated and standardized drug susceptibility testing (DST) is required to improve patient care. This multicountry, multilaboratory external quality assessment (EQA) study aimed to validate the sensitivity, specificity, and reproducibility of provisional bedaquiline MIC breakpoints and World Health Organization interim critical concentrations (CCs) for categorizing clinical isolates as susceptible/resistant to the drug. Three methods were used: Middlebrook 7H11 agar proportion (AP) assay, broth microdilution (BMD) assay, and mycobacterial growth indicator tube (MGIT) assay. Each of the five laboratories tested the 40-isolate (20 unique isolates, duplicated) EQA panel at three time points. The study validated the sensitivity and specificity of a bedaquiline MIC susceptibility breakpoint of 0.12 μg/ml for the BMD method and WHO interim CCs of 1 μg/ml for MGIT and 0.25 μg/ml for the 7H11 AP methods. Categorical agreements between observed and expected results and sensitivities/specificities for correctly identifying an isolate as susceptible/resistant were highest at the 0.25, 0.12, and 1 μg/ml bedaquiline concentrations for the AP method, BMD (frozen or dry plates), and MGIT960, respectively. At these concentrations, the very major error rates for erroneously categorizing an isolate as susceptible when it was resistant were the lowest and within CLSI guidelines. The most highly reproducible bedaquiline DST methods were MGIT960 and BMD using dry plates. These findings validate the use of standardized DST methodologies and interpretative criteria to facilitate routine phenotypic bedaquiline DST and to monitor the emergence of bedaquiline resistance.